THE USE OF DIGITAL MEDIA IN ONLINE ASSESSMENT - FURQON EDI WIBOWO, M.Pd
The objectives of this study are to describe the use of digital media in EFL Students’ online assessment and to find out the students’ perception in use of digital media in online assessment. The method used in this study is descriptive qualitative and the techniques of collecting the data used observation and interview. The results showed that the online assessment in English lesson was implemented through the use of six digital media, namely Google Form, Google Classroom, Kahoot, Instagram, TikTok, WhatsApp, and YouTube. Google form and Google Classroom were used for arranging, creating, submitting, and correcting the assessment. Instagram and WhatsApp were used for giving and submitting the assessment while YouTube was used for giving example to students. The students had a positive attitude as well about the use of digital media in online assessment. They agreed that introducing technology into the way to do evaluations is a positive innovation since it allowed them to receive immediate feedback and result. The findings revealed that the students think Google Form is simple to use during the implementation, which is supported by respondents when interviewed about it. Students' perspectives on the implementation of Google Forms are valuable for making it easier for users to create and collect data they want. It also demonstrated that numerous types of social media, such as YouTube, Instagram, TikTok while WhatsApp are quite interesting because they are frequently utilized in daily life.